Synthesis of Monofluoroalkene-Based Dipeptide Bioisosteres via Regioselective Ring Opening of 1,1-Difluorocyclopropanes - Fuchibe, Kohei; Mitsumori, Masashi; Ishikawa, Kai; Ichikawa, Junji (Synthesis, 2025)
Monofluoroalkene-based dipeptide bioisosteres were synthesized via (I) difluorocyclopropane ring opening and (II) SN2′-type defluorination. (2,2-Difluorocyclopropyl)methyl acetates were treated with acetonitrile in the presence of trifluoromethanesulfonic acid (triflic acid, TfOH). Elimination of acetic acid resulted in regioselective cleavage of the C–C bond distal to the CF2 moiety (ring opening), and then a Ritter-type N-terminal introduction afforded N-(2,2-difluorohomoallyl)acetamides. The obtained difluoroacetamides underwent allylic substitution of bromine for fluorine in an AlBr3/CuBr system to generate 3-fluoroallylic bromides, whose substitution with n-Bu4NCN facilitated C-terminal introduction. Conversion of the cyano group into a carbamoyl group afforded the desired monofluoroalkene-based dipeptide bioisosteres.
Keywords: alkenes; amides; bioisosteres; C–C bond cleavage; cyclopropanes; fluorine; Ritter reaction